Study on the Atmospheric Corrosion Resistance of H-Beam Weathering Steel - YAN Ting, GAO Xiu-hua, HAN Lei-lei, WU Hong-yan, DU Lin-xiu, LI Tong (Cailiao Baohu, 2021)
In order to study the influence of H-beam weathering steel microstructures formed with various cooling processes on the atmospheric corrosion resistance, H-beam weathering steel after hot-rolling were cooled down with three methods of air cooling, furnace cooling and water cooling, and three kinds of microstructures, ferrite + bainite, ferrite + pearlite and bainite, were obtained respectively. In addition, alternate immersion test was used to study the corrosion behavior of weathering steel with different microstructures in atmospheric environment. The corrosion performance of samples with rust after corrosion were evaluated by weightlessness analysis and electrochemical experiments. Moreover, the morphology of the corrosion products and the distribution of the rust layer elements were analyzed, and the phase composition of the corrosion products was analyzed by XRD. Results showed that at the initial stage of corrosion, the rust layer of single-phase bainitic microstructure was the most compact, and its atmospheric corrosion resistance was the best; at the later stage of corrosion, the corrosion resistance of weathering steels with different microstructures was roughly the same.